Anaerobic critical velocity of master swimmers - Espada, Mário (2014)
Based on the concept of critical velocity (CV), a new trend has been suggested with the aim to determine anaerobic performances. Using short distances trials, the concept of anaerobic critical velocity (AnCV) seems to represent the functional anaerobic capacity of swimmers. Marinho et al. (2011) found a linear relationship between AnCV and 50 m swimming performance (S50) in young swimmers, suggesting that AnCV could be a relevant parameter to monitor and prescribe anaerobic training sets. The purpose of this study was to analyze the relationship between AnCV and swimming performance in master swimmers. Also, ascertain if AnCV may be determined based in two or three swimming distances, 15, 25 and 50 m (T15, T25 and T50, respectively).